PEMBERDAYAAN MASYARAKAT BERBASIS LINGKUNGAN HIDUP DI DESA MARGALAKSANA KABUPATEN BANDUNG BARAT - Priyo Subekti; Yanti Setianti; Hanny Hafiar (Universitas Gadjah Mada, 2018)
The empowerment approach becomes the main base of West Bandung Regency Government in the development of society to welcome the development of industrial estate. Empowerment has the meaning of generating resources, opportunities, knowledge, and skills to increase capacity in determining the future. Researchers are interested in conducting initial mapping in advance about environmental conditions, socio-economic conditions, government policies, responses, and community needs related to the development of industrial parks. The community empowerment conducted by the working group working together with the agriculture department, Disperindag, and BPWC and getting full support from the village of Margalaksana itself. There are many activities conducted by the working group by utilizing the natural potential that exist in Margalaksana Village. Some potentials of the Community Empowerment Program in Margalaksana Village: 1) The potency of fish using floating net pond in Cirata reservoir; 2) The potency of batik; 3) The potency of water hyacinth waste; and 4) The potency of tourism. Human capital plays a major role in as a modifying factor of community resources in achieving the success of the empowerment process. Good human capital is characterized by the level of education that able to provide motivation so as to develop independence in the community.